Effect of Vegetation Diversity on Erosion Rate - Sarminah, Sri; Prititania, Farha Shera; ., Karyati (Agrifor : Jurnal Ilmu Pertanian dan Kehutanan, 2018)
The climate in Indonesia is a tropical climate with high rainfall, making Indonesia vulnerable to erosion. In addition to high rainfall, vegetation, slope and soil types also affect erosion. This study aims to determine the Important Value of Species (NPJ), the relationship between rainfall and surface runoff and the mass of eroded soil and the level of erosion hazard at different vegetation densities. Important Value The highest types of the three dominating types in plot I were Schima wallichii 115.12%, Macaranga gigantea 69.38% and Cratoxylum sumatranum 44.69%. Whereas in plot II the highest NPJ value of three types dominates, namely Macaranga gigantea 59.13%, Litsea angulata 39.52% and Aquilaria mallacensis 35.37%. The amount of eroded soil mass that occurred in PUE I was 0.13 tons / ha / year and PUE II was 0.19 tons / ha / year. Simple linear analysis of the relationship between rainfall and eroded soil mass at PUE I has a correlation value (r) = 0.79 with the equation Y = -8.34 + 0.39X, whereas in PUE II the correlation value (r) = 0.90 with the equation Y = -12.96 + 0.56X. The danger level of erosion (TBE) in PUE I and PUE II was very mild (erosion rate <15 tons / ha / year, Bahya Erosion I class with soil solum depth> 90 cm).